Eco-literacy components on Kurikulum Merdeka: 5th-grade elementary school’s IPAS textbook analysis - Kartika Nofiyanti; Yulia Maftuhah Hidayati (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The study was conducted to analyze eco-literacy components in Kurikulum Merdeka, especially those contained in IPAS textbooks for grade 5th elementary school students, to facilitate the development of students' environmental literacy skills. The method for this study uses a qualitative approach, with data collection using content analysis techniques. Test the validity of the data using an expert judgment approach. The research finding that the six components of eco-literacy have been included in Kurikulum Merdeka, in the IPAS textbook for grade 5th elementary school students. There are many Cognitive Knowledge components and Knowledge of Environmental Issues components in books, but the Affection components, Ecological and Natural History knowledge components, Socio-political Knowledge components, and Environmentally Responsible Behavior (ERB) components still receive less attention. The results of this study from the analysis of eco-literacy components suggest that there should be further study and development regarding eco-literacy-based learning media to support eco-literacy education in Indonesia. AbstrakKajian ini dilakukan guna menganalisis komponen ekoliterasi pada Kurikulum Merdeka, terutama yang termuat dalam buku teks Ilmu Pengetahuan Alam dan Sosial (IPAS) siswa kelas V Sekolah Dasar, sehingga dapat memfasilitasi pengembangan kecakapan literasi ekologi siswa. Jenis metode kajian ini adalah pendekatan kualitatif dimana teknik pengumpulan datanya menggunakan desain analisis isi (Content Analysis). Metode keabsahan data yang digunakan adalah penilaian ahli (Expert Judgement). Hasil kajian ini menunjukkan bahwa enam komponen ekoliterasi telah termuat pada Kurikulum Merdeka, yaitu di dalam buku teks IPAS siswa kelas V Sekolah Dasar. Komponen Pengetahuan Kognitif serta Komponen Pengetahuan terhadap Masalah dan Isu Lingkungan merupakan komponen yang banyak ditemukan di dalam buku teks. Namun, komponen Afeksi, Pengetahuan Ekologi dan Sejarah Alam, Pengetahuan Sosial-Politik, serta Komponen Perilaku Bertanggung Jawab terhadap Lingkungan masih belum banyak mendapatkan perhatian. Hasil dari kajian tentang analisis komponen ekoliterasi ini menyarankan adanya kajian dan pengembangan lebih lanjut terkait media pembelajaran berbasis ekoliterasi untuk mendukung pendidikan literasi lingkungan di Indonesia.Kata Kunci: Buku teks; ekoliterasi; Kurikulum Merdeka; Ilmu Pengetahuan Alam dan Sosial (IPAS)